An assessment of trace element contamination in groundwater aquifers of Saharanpur, Western Uttar Pradesh, India. (July 2019) - Kumar, Amrish; Bharti,; Malyan, Sandeep K.; Kumar, Smita S.; Dutt, Dharm; Kumar, Vivek
Abstract: Groundwater is a vital natural resource needed for the growth and development of life on the Earth. The aim of the present study was to estimate trace elements concentration in groundwater and their effect on human health in Saharanpur district, Uttar Pradesh, India. Groundwater samples were collected from the government hand pumps and analyzed for eight trace elements using ICP-MS. In all the samples, concentrations of two trace elements namely Hg and Fe were above the drinking water limits (mean values of 2.04 ± 1.94 and 1531 ± 1372 μg/L, respectively) as specified by Bureau of Indian Standards (2012) and World Health Organization (2011). For Cr and Pb, 10% and 15% of the groundwater samples respectively, were above the specified limits. The concentration of As, Cd, and Zn was within limits as specified for drinking water. Hazard Quotient (HQ) for the assessment of human health showed no potential adverse health risk except Fe. This study showed that the value of the Hazard Index (HI) for all the samples was also within limits except for one of the sampling sites (#S9). HQ and HI values were almost equivalent to permissible limits at the majority of sites. However, on the basis of cumulative results obtained during the study, it was concluded that urgent management actions are required to protect future groundwater quality of this region.